Contenidos informativos de la Radio Runacunapac y su percepción en la audiencia comunitaria de la parroquia Simiatug, cantón Guaranda, en el periodo julio -noviembre 2024, - Huilca Morocho, Ana Cristina (2025)
Communication sources such as radio as a means of communication play a very important role, as they assist people in disseminating information that impacts their daily lives. News not only provides information, but also acts as essential tools in decision-making by generating viewpoints on relevant issues of common interest, as well as for community development. For this research, we focused on a sample value of 370 individuals from the community who participated in the study. Based on their responses and perceptions, we have determined how radio content is perceived by the community. The community radio station and its informative programs are essential for providing residents with clear and understandable information. Runacunapac Community Radio is a prominent example committed to providing high-quality content, tailored to the specific demands and interests of its audience.This study aims not only to examine what kind of information the radio disseminates, but also to deeply understand how listeners appreciate and perceive it. With this perspective, we aspire to contribute to a better understanding of the relationship between the radio and its audience, as well as to identify areas that can be optimized for the information to be more relevant and generate a greater impact. This analysis is essential to strengthen the bond between the radio and the community, ensuring that the informative content broadcasted by Radio Runacunapac truly serves to educate, inform, and improve the perception of its listeners.